Age and hafnium isotopic evolution of the Didesa and Kemashi Domains, western Ethiopia - Blades, M.; Collins, A.; Foden, J.; Payne, J.; Xu, X.; Alemu, T.; Woldetinsae, G.; Clark, Christopher; Taylor, R. (2015)
The Western Ethiopian Shield (WES) forms a vast, underexplored, region of the East African Orogen. Lying towards the west of the orogen and between the dominantly juvenile Arabian-Nubian Shield in the north and the high-grade Mozambique Belt to its south, it holds a key position; vital in understanding the role of the East African Orogen in Gondwana formation. The WES is made up of a range of supra-crustal and plutonic rocks that formed in Tonian volcanic arc environments. The relative timing and duration of arc formation within the East African Orogen is still slowly being unravelled and we present new U-Pb and Hf isotopic data from zircons that help to define the maximum depositional age and provenance of the protoliths to meta-sedimentary units, as well as constrain the age of igneous intrusions located within the WES. Detrital zircons, obtained from a meta-sandstone, yield provenance age peaks at 2.8–2.4 Ga, ca. 1.8 Ga and 1.15–0.84 Ga and a maximum depositional age of 838 ± 13 Ma. Hafnium isotopes from the same zircons demonstrate that both the oldest and youngest populations have broadly juvenile Hf isotopic values.However, the ca. 1.8 Ga population shows significantly evolved Hf isotopic values. Sensitive High Resolution Ion MicroProbe (SHRIMP) U-Pb ages from two granites and a felsic granite and hornblende + biotite tonalite in the Nekempt–Ghimbi region of the Western Ethiopian Shield (Didesa and Kemashi Domains) indicate two pulses of magmatism at 850–840 Ma and 780–760 Ma. Partial melting and deformation in the Didesa Terrane occurred at ca. 660 Ma. Further west, the post-tectonic Ganjii granite yielded a 206Pb/238U age of 584 ± 10 Ma, constraining pervasive deformation in the area. Age constraints on orogenesis in the Western Ethiopian Shield (ca. 660 Ma) are similar to those in NE Uganda (ca. 690–660 Ma), but are older than the Ediacaran peak orogenesis reported from the Southern Ethiopian Shield, Eritrea and northern Ethiopia and from SE Kenya. This suggests that closure of the western Mozambique Ocean involved progressive volcanic-arc accretion to the active margin of Cryogenian–Ediacaran Africa.